Effects of bioactive components of Pu-erh tea on gut microbiomes and health: A review. (15th August 2021) - Liu, Jun-Yu; He, Dong; Xing, Yi-Fan; Zeng, Wen; Ren, Kai; Zhang, Chong; Lu, Yuan; Yang, Song; Ou, Shu-Jian; Wang, Yi; Xing, Xin-Hui
Highlights: The main components of ripe Pu-erh tea were reviewed. The interaction between each component and gut microbiomes (GMs) was summarized. The Pu-erh tea function is corresponding to the representative quality indicators. Establishment of a clue of "components - GMs - representative quality indicators". Helpful to future standardization of Pu-erh tea industry. Abstract: Pu-erh tea is a post-fermentation tea with unique flavor and multiple health benefits. Due to the various microorganisms involved in the post-fermentation process, Pu-erh tea contains highly complex components, which have rich interactions with the gut microbiomes (GMs). Because the structure and homeostasis of GMs are closely related to human wellness and the various diseases progress, the beneficial effects of Pu-erh tea on GMs have a great potential for application in health care. However, there is no systematic summary of the bioactive components of Pu-erh tea, and their effects on the GMs. Here, we review the current studies on the effects of Pu-erh tea and its bioactive components on the structure of GMs as well as on health improvement, and further discuss the relevant quality indicators. This "components – function - indicators" clue will hopefully stimulate the standardization of Pu-erh tea fermentation process and the development of its functional products.